The Impact Of Budget Participation On Work-Information Availability -The Role Of Organizational Commitment, Distributive Fairness And Satisfaction- -An Empirical Study On The Agricultural Firms- - Hatem, Iyad Malek; Saeed, Ahed Ali (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The main objective of this study is to examine the direct impact of the relationship between information availability needed to prepare budget and participating in budget preparation process, as well as the indirect impact of this relationship. More specifically, this study will examine the impact of participating in budget preparation process on psychological factors of the participants such as commitment, justice and satisfaction. Besides, this study will further examine the impact of these factors on information availability. To achieve the study objectives, a questionnaire was used and distributed on the Agricultural Firms in the Syrian Coast. This questionnaire was distributed to 72 respondents, but only 50 questionnaires were completed and received. The results show a positive impact of the relationship between information availability needed to prepare budget and participating in budget preparation process, as well as a positive impact of participating in budget preparation process on psychological factors of the participants. Additionally, the results indicate a positive impact of the information content of psychological factors on participating in budget preparation process. هدفت الدراسة إلى تحديد الأثر المباشر للمشاركة في إعداد الموازنة على توافر المعلومات اللازمة للقيام بالعمل, ثم تحديد الأثر غير المباشر لهذه العلاقة؛ وذلك من خلال دراسة أثر المشاركة في إعداد الموازنة على العامل النفسي للمشاركين, والمتمثل بالشعور بالالتزام وبالعدالة وبدرجة الرضا, فضلاً عن تحديد أثر كل من هذه المتغيرات على توافر المعلومات. لذلك تمَّ إجراء مسح ميداني باستخدام الاستبانة على منشآت القطاع الزراعي العامة العاملة في الساحل السوري, إذ تمَّ توزيع /72/ استبانة, استرجع منها /50/ استبانة. وقد أظهرت نتائج تحليل البيانات وجود تأثير إيجابي للمشاركة في إعداد الموازنة على توافر المعلومات, وتأثير إيجابي للمشاركة في إعداد الموازنة على متغيرات الجانب النفسي الناتجة عن هذه المشاركة, فضلاً عن وجود تأثير إيجابي جداً لهذه المتغيرات على الجانب المعلوماتي المرتبط بعملية المشاركة.